Pengaruh Variasi Konsentrasi Indole Butyric Acid (IBA) Pada Anggrek (Dendrobium hybrid) Terhadap Survival dan Pertumbuhan Dalam Media Arang - Niakurrotul A'yun Firdausy; Tintrim Rahayu; Gatra Ervi Jayanti; Dita Agisimanto (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
One of the most popular types of orchids by the public is the Dendrobium Orchid. One of the functions of adding growth regulators is Indole Butyric Acid (IBA) which functions to accelerate root growth. The content possessed by IBA can cause additional roots under certain conditions. This study aims to determine the optimal variation of the concentration of the hormone Indole Butyric Acid (IBA) on the growth of Dendrobium hybrid orchids. Acclimatized Dendrodium hybrid seedlings were selected first, planted on charcoal media, and treated twice a week for two months using an IBA concentration of 0.25; 0.50; 0.75; and 1 ml/L. In this study, the optimal concentration of IBA with root length parameters was at a concentration of 1 ml/L with an average of 2.33. For a concentration of 0.75 ml/L with the parameter of the number of new roots having an average of 1.94 and the parameter of the number of leaves having an average of 1.85. Plant length with a concentration of 0.50 ml/L had an average of 2.56. The concentration of 0.25 ml/L with leaf length parameter has an average of 1.94 while the wet weight parameter has an average of 1.04. For the effect of giving IBA hormone on survival, the most optimal concentration was 0.75 ml/L with 91% live and 9% dead.